(untitled) (Journal of Scientific Research, 2011)
Bangladesh is one of the tea producing countries of the world. It has 163 tea estates. Rangapani is a low yielding tea estate relative to other neighboring tea estates of Chittagong district in Bangladesh. A total 54 soil samples were collected from six different hills and three topographic positions having different depths of Rnagapanni Tea-Estate. Physico-Chemical properties of soils such as active acidity, reserve acidity, cation exchange capacity and clay content of the collected soil samples were determined. The measured parameters of the soil samples were plotted and analyzed with reference to site and topography. The parameters have been found to vary with sampling sites, depths and topography. Active acidity and reserve acidity were very low, with some exceptions compared to the optimum range for tea cultivation. Sand, silt, clay and cation exchange capacity (CEC) were found in reasonable range Keywords: Soil; Active acidity; Reserve acidity; Cation exchange capacity; Clay content. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: 10.3329/jsr.v3i3.7503 J. Sci. Res. 3 (3), 683-688 (2011)